Tectonics of Volcanogenic Massive Sulphide (VMS) Deposits at Flores Back Arc Basin: A Review - Noor Cahyo Dwi Aryanto; Hananto Kurnio (BULLETIN OF THE MARINE GEOLOGY, 2020)
The bathymetry, petrology, marine magnetic, and seismic-SBP data have identified the northwest-southeast direction submarine ridge that shows hydrothermal activity. This activity occurred through Mount Baruna Komba, Abang Komba, and Ibu Komba. The volcanic rocks are andesite basaltic lava flows, tuff, and pumice. The andesite basaltic lava shows porphyritic, intergranular, intersertal to glomeroporphyritic textures. The rock composes anhedral minerals of k-feldspar, plagioclase, and pyroxene. These minerals present in small-sized, short prismatic dispersed in very fine groundmass minerals or glasses. Most of the volcanic rocks have experienced various degrees of alteration. The k-feldspar and plagioclase are most dominantly transformed into sericite, clay mineral, carbonate, epidote and oxide mineral, opaque mineral, and secondary plagioclase through the albitization process, while pyroxene replaced by chlorite. Other minerals are biotite and quartz, and base metals are present Cu, Zn, Ag, As, Pb, and gold. Mineralization categorizes as the phyllic zone, sub-prophylithic zone, and phyllic-potassic zone that formed at a temperature range of 250-400oC. The submarine hydrothermal alteration in the Komba Ridge is associated with a volcanogenic sulphide deposit controlled by crust thinning due to the crust rifts in the back-arc tectonic setting.Keywords: volcanic rocks, submarine hydrothermal alterations, Komba ridge, volcanogenic massif sulphide (VMS), back-arcData batimetri, petrologi, magnetic laut dan seismic-SBP telah memetakan dan mengidentifikasi suatu punggungan bawahlaut berarah baratlaut-tenggara yang memperlihatkan aktifitas hidrotermal bawah laut. Aktifitas tersebut muncul melalui Gunung Baruna Komba, Abang Komba dan Ibu Komba. Batuan gunungapi penyusun adalah aliran lava andesit basaltic, tuf dan pumis. Lava andesit basaltik memperlihatkan tekstur porfiritik, intergranular, intersertal to glomeroporfiritik. Mineral penyusun berupa k-felspar, plagioklas, dan piroksen dalam bentuk mineral anhedral, prismatik pendek berukuran kecil yang berada dalam masa dasar mineral sangat halus atau gelas. Batuan vulkanik telah mengalami ubahan dalam berbagai tingkat, dimana k-flespar dan plagioklas paling dominan terubah menjadi serisit, lempung, karbonat, epidot dan mineral oksida, opak atau plagioklas sekunder melalui proses albitisasi sedangkan piroksen mengalami proses ubahan digantikan oleh klorit. Mineral ubahan lainnya adalah biotit dan kuarsa dan logam dasar seperti Cu, Zn, Ag, As, Pb, dan emas. Mineralisasi dikategorikan sebagai zona filik, zona sub-profillitik, dan zona filik-potasik yang terbentuk pada kisaran suhu 250-400oC. Alterasi hidrotermal bawah laut di Punggungan Komba berasosiasi dengan suatu endapan sulfida volkanogenik yang dikontrol oleh penipisan kerak akibat peregangan kerak dalam tatan tektonik busur belakang.Keywords: batuan gunungapi, alterasi hidrotermal bawah laut, punggungan Komba, sulfida massif vulkanogenik, busur belakang